Frequency of Postpartum Depression in Patients Undergoing Caesarean Section: Postpartum Depression in Patients Undergoing Caesarean Section - Iqbal, Sidra; Akram, Umbreen; Momana, Shehzad Bashir; Shaheen, Zubaida (Pakistan Journal of Health Sciences, 2025)
Postpartum depression (PPD) is a common mental health disorder affecting women after childbirth, but its risk varies across clinical and obstetric contexts. However, evidence regarding the association between CS-related maternal, socioeconomic, surgical, and neonatal factors and the development of PPD remains inconsistent. Objectives: To determine the frequency of PPD among women undergoing Caesarean section and its association with education level, socioeconomic status, type of Caesarean section, complications, history of mental health issues, and neonatal complications. Methods: This descriptive cross-sectional study was conducted at the Combined Military Hospital (CMH) Quetta from February 2025 to June 2025. A total of 91 postpartum women who delivered via Caesarean section were included using non-probability consecutive sampling. Data were collected using the Edinburgh Postnatal Depression Scale (EPDS) with a cutoff score of ≥13 to define PPD. Statistical analysis was performed using SPSS version 26.0, and associations between PPD and categorical variables were assessed using the chi-square test. Results: The mean age of participants was 32.14 ± 8.34 years, and the average parity was 2.52±1.68. Postpartum depression was identified in 22 (24%) women. Stratified analysis showed no statistically significant association between PPD and education level (p=0.864), socioeconomic status (p=0.493), type of Caesarean section (p=0.978), complications (p=0.656), history of mental health issues (p=0.794), or neonatal complications (p=0.895). Conclusions: The prevalence of PPD among women undergoing Caesarean section was 24%. However, no significant associations were found with maternal, socioeconomic, surgical, or neonatal factors (all p>0.05). Routine screening and psychological support are essential to address PPD effectively.